EFFECTIVENESS OF AUTOGENIC RELAXATION ON STRESS AND BIO PHYSIOLOGICAL PARAMETERS AMONG ADOLESCENTS - PILOT REPORT - MS.S.SUJITHRA, (International Journal of Pharma and Bio Sciences, 2016)
Stress is the common psychiatric problems found in adolescent in present scenario, if untreated or undiagnosed can lead to future consequences both for the individual and for the society. Hence a self-help strategy is to be taught for adolescents to stabilize their level of stress by themselves. Adolescents at selected residential homes using true experimental research design are selected by simple random sampling technique for pre-test post-test control group design. The study was conducted among 30 adolescent at selected homes. It shows that, when comparing the level of stress during pre-test in experimental group majority(66.7%) of the adolescence had moderate stress and also the percentage of adolescence with severe stress were 13.3% and in control group also majority (86.7%) adolescence had moderate level of stress and also the percentage of adolescence with severe stress were 13.3% eventually .But, when comparing the level of stress during post-test in experimental group majority(66.7%) of the adolescence had moderate stress and no adolescent had severe stress whereas in control group majority (93.3%) adolescence had moderate level of stress and also the percentage of adolescence with severe stress were 6.7%.Hence the Autogenic Relaxation was found to be effective in reducing the level of stress among adolescent in residential homes.